Preparation of porous carbon materials by polyphosphazene as precursor for sorption of U(VI) - Liu, Xiaopeng (2021)
Polyphosphazene was synthesized by ultrasonic using 4,4-diaminodiphenyl ether and hexachlorocyclotriphosphazene (HCCP) as precursors. Next, it was further carbonized and functionalized to prepare the carboxylic-acid functionalized N, P co-doped carbon materials (NPCs-COOH). The structure of NPCs-COOH was characterized by FTIR, SEM and XPS. The sorption performance of NPCs-COOH for U(VI) in solution were determined under diverse factors including pH values, initial concentration, equilibrium time and reaction temperature. The results indicated that the optimal pH value was 5.0 and the equilibrium time was 60.0 min. The maximum sorption capacity from experimental results was 425.16 mg/g. The analysis results of the sorption thermodynamics and kinetics showed that the NPCs-COOH had excellent sorption performance so that it can be utilized on removal of U(VI) effectively in aqueous solution.